Exploring the potential of design-based research in improving Myanmar's healthcare education system - Aung, Khin Thandar; Aung, Thurein (IGI Global Scientific Publishing, 2025)
The healthcare education system in Myanmar faces challenges such as outdated curricula, limited resources, and insufficient training opportunities. To address these issues, an innovative approach like Design-Based Research (DBR) can be explored. DBR integrates theory and practice through iterative development cycles, emphasising problem-solving, collaboration, and educational interventions. DBR prioritises flexibility and adaptability to create contextually relevant tools and curricula for Myanmar's healthcare needs. This chapter presents a roadmap for implementing DBR in Myanmar's healthcare education system, highlighting its capacity to enhance training quality, address resource allocation disparities, and foster continuous improvement. By leveraging DBR, Myanmar's healthcare education system can become more responsive, contemporary, and capable of producing professionals who can meet diverse population needs. This approach is vital as thecountry modernizes its healthcare system and improves public health outcomes, especially in underserved rural areas.